Ordered self-assembled monomolecular layer, semitransparent solar cell and preparation method thereof

The self-assembled single molecule layer is prepared by mixing carbazole phosphate compounds with solvents in translucent perovskite solar cells, which solves the problem of preparing dense ordered layers and improves the efficiency and stability of the solar cell.

CN119604167APending Publication Date: 2025-03-11WUHAN UNIV OF TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411589163.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

It is difficult to prepare dense and ordered self-assembled single-molecule layers in the prior art, affecting the performance and stability of translucent perovskite solar cells.

Method used

By mixing the carbazole phosphate compound with an appropriate solvent, a mixed solution is prepared and after film formation on the substrate, a dense and orderly self-assembled monolayer is obtained.

Benefits of technology

The density and order of self-assembled single-molecule layer are achieved, the perovskite nucleation activation energy is reduced, and the efficiency and stability of translucent perovskite solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604167A_ABST
    Figure CN119604167A_ABST
Patent Text Reader

Abstract

The invention relates to an orderly self-assembled monomolecular layer, a semitransparent solar cell and a preparation method of the semitransparent solar cell. The preparation method comprises the following steps: uniformly mixing carbazole phosphoric acid MeO-2PACz with an isopropanol solvent to obtain a mixed solution, spin-coating the mixed solution on an ITO transparent conductive substrate, and annealing to obtain a uniform and compact self-assembled monomolecular layer. And sequentially preparing a perovskite light absorption layer, a C60 electron transport layer, a SnO2 buffer layer and an ITO transparent electrode layer on the surface of the self-assembled monomolecular layer by adopting spin coating, vacuum evaporation, atomic deposition, magnetron sputtering and the like, and finally obtaining the semitransparent perovskite solar cell. The uniform and compact high-quality self-assembled monomolecular layer can be prepared by using the isopropanol and MeO-2PACz spin coating liquid formula, so that the nucleation activation energy of perovskite can be reduced, the perovskite buried layer is more compact, the charge recombination reaction of the buried interface is reduced, and the photoelectric conversion efficiency is improved. And the efficiency and the stability of the semitransparent perovskite solar cell device are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite functional materials and solar cells, and in particular to an ordered self-assembled monolayer, a semi-transparent solar cell and a preparation method thereof. Background Art

[0002] Semi-transparent perovskite solar cells (ST-PSCs) have the advantages of light transmittance, high performance and low cost, and can be used as integrated smart windows for buildings and vehicles. In addition, integrating semi-transparent wide-bandgap perovskites as top cells with narrow-bandgap bottom cells (such as crystalline silicon, copper indium gallium selenide cells, tin-based perovskite cells, and organic photovoltaic cells) can produce highly efficient and industrially compatible tandem solar cells. However, for wide-bandgap perovskites, Br - and I - The different ionic properties will affect the crystallization behavior of the precursor solution, resulting in uneven surface morphology and significant changes in bulk composition of mixed halide wide-bandgap perovskites, leading to problems such as non-radiative recombination and poor stability.

[0003] The application of self-assembled monolayers enables semi-transparent batteries to have high hole selectivity, thus achieving high performance. However, how to prepare dense and ordered self-assembled monolayers is particularly critical. The self-assembled monolayers that have been publicly reported are mainly prepared by spin coating. Due to the solvation effect, the self-assembled monomolecules in the precursor solution used for spin coating will inevitably interact with the solvent molecules. The properties of the solvent affect the binding of the self-assembled monomolecules on the conductive substrate, which is not only not conducive to the formation of an ordered and dense monomolecular hole transport layer, but also affects the preparation quality of the subsequent perovskite absorption layer. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art, and to provide a method for preparing an ordered self-assembled monolayer, comprising: uniformly mixing a carbazole phosphate compound with a solvent to obtain a mixed solution, then using the mixed solution to form a film on a substrate, and finally fully annealing the wet film to obtain a dense and ordered self-assembled monolayer. The carbazole phosphate compound is specifically a nitrogen-containing heterocyclic phosphoric acid derivative, selected from any one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), preferably MeO-2PACz; the solvent is selected from any one of ethanol (EtOH), isopropanol (IPA), and acetone (AC), preferably IPA.

[0005] Furthermore, the concentration of the carbazole phosphoric acid in the mixed solution is 0.3-1 g / L.

[0006] Furthermore, a film is formed on the substrate by spin coating, the spin coating speed of the mixed solution is 2000-5000 rpm, and the spin coating time is 20-50s.

[0007] Furthermore, the annealing temperature is 90-140° C., and the annealing time is 10-50 min.

[0008] The second object of the present invention is to provide a self-assembled monolayer prepared according to the above method, whose water contact angle is not higher than 60°. The self-assembled monolayer is tightly bonded to the substrate, and the number of molecules covered per unit area is greater than 10 15 molecules / cm 2 .

[0009] The third object of the present invention is to provide an application of the self-assembled monolayer as a hole transport layer in a semi-transparent perovskite solar cell.

[0010] Furthermore, the semi-transparent perovskite solar cell has a multi-layer composite structure, which includes a transparent conductive substrate layer, a self-assembled monolayer, a perovskite light absorption layer, an electron transport layer, a buffer layer and a TCO transparent electrode layer in sequence.

[0011] Furthermore, the specific process of this application is as follows: first, a self-assembled monolayer is prepared on a transparent conductive substrate according to the above method, and then a perovskite light-absorbing layer is prepared on the self-assembled monolayer by spin coating, and then an electron transport layer is prepared on the perovskite light-absorbing layer by vacuum evaporation, and then a buffer layer is prepared on the electron transport layer by atomic deposition, and finally a TCO transparent electrode layer is prepared on the buffer layer by magnetron sputtering.

[0012] Furthermore, the perovskite light-absorbing layer is obtained by spin coating a perovskite precursor solution on a self-assembled monolayer and annealing, wherein the solute of the perovskite precursor solution is Cs 0.05 FA 0.73 MA 0.22 PbI 2.31 Br 0.69 The solvent is a mixture of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 3-5:1, and the concentration of the perovskite precursor solution is 1.4-1.6M.

[0013] Furthermore, the spin coating speed for preparing the perovskite light absorbing layer is 3000-5000 rpm, the total spin coating time is 30-50 s, ethyl acetate anti-solvent is added to the wet film surface 10-15 s before the end of spin coating, the annealing temperature after the end of spin coating is 90-120°C, and the annealing time is 20-50 min. The perovskite light absorbing layer thus prepared has a band gap of 1.68 eV.

[0014] Furthermore, the transparent conductive substrate is specifically an ITO transparent glass substrate.

[0015] Furthermore, the material of the electron transport layer is C60, and its thickness is 20-30 nm.

[0016] Furthermore, the material of the buffer layer is SnO2, and its thickness is 10-30nm.

[0017] Furthermore, the TCO transparent electrode layer is specifically an ITO transparent electrode, and its thickness is 100-300nm.

[0018] The present invention selects isopropanol with appropriate polarity from a variety of solvents to prepare a uniform and compact self-assembled monomolecular hole transport layer, which is used to reduce the nucleation activation energy of perovskite, making the perovskite buried layer more compact, thereby reducing the charge recombination reaction at the buried interface. In addition, the self-assembled monomolecular hole transport layer is applied to semi-transparent perovskite solar cells, significantly improving the efficiency and stability of the device, and has good application prospects in the fields of building photovoltaic integration and stacked cells.

[0019] Compared with existing similar products or technologies, the improved effects of the present invention are mainly reflected in the following aspects:

[0020] (1) The carbazole phosphate molecules are dissolved in isopropanol solvent. The medium polarity isopropanol is more conducive to the chemical bonding between the carbazole phosphate molecules and the transparent conductive substrate, and can form a more uniform and denser self-assembled monolayer.

[0021] (2) The self-assembled monolayer reduces the activation energy of the perovskite nucleation process, ensuring that the buried surface of the perovskite film is denser and has fewer defects, thereby increasing charge transfer and reducing carrier recombination reactions at the buried interface.

[0022] (3) The semi-transparent solar cells made based on the self-assembled monolayer have high efficiency and good stability, which provides a technical reserve for the commercial application of semi-transparent perovskite solar cells and can be widely used in many different fields such as building photovoltaic integration and stacked cells.

[0023] (4) The present invention solves the problem in the prior art that it is difficult to form a high-quality self-assembled monolayer, and the entire preparation method is relatively simple, easy to implement, and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is an X-ray photoelectron spectrum of the MeO-2PACz self-assembled monolayer on the ITO conductive substrate prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0025] Figure 2 The water contact angle test photos of the MeO-2PACz self-assembled monolayer prepared in Example 1 and Comparative Examples 1-2 of the present invention are shown.

[0026] Figure 3 The contact angle photographs of the perovskite precursor solution of the MeO-2PACz self-assembled monolayer prepared in Example 1 and Comparative Examples 1-2 of the present invention.

[0027] Figure 4 The coverage density diagram of the MeO-2PACz self-assembled monolayer on the ITO conductive substrate prepared in Example 1 of the present invention and Comparative Examples 1-2 is shown.

[0028] Figure 5 This is a SEM image of the interface of the perovskite buried bottom of the MeO-2PACz self-assembled monolayer deposited on the ITO conductive substrate prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0029] Figure 6 This is a current-voltage diagram of the semi-transparent perovskite solar cell prepared in Application Example 1 of the present invention.

[0030] Figure 7 This is the MPP output diagram of the semi-transparent perovskite solar cell prepared in Application Example 1 of the present invention.

[0031] Figure 8 This is a physical picture of the small-scale semi-transparent perovskite solar cell module prepared in Application Example 2 of the present invention.

[0032] Fig. 9 This is a current-voltage diagram of a small-scale semi-transparent perovskite solar cell module prepared in Application Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, the following is further described in conjunction with specific embodiments and drawings. It should be noted that the following embodiments and application examples are only partial implementation methods of the present invention and not all, and simple replacements or improvements made without departing from the main purpose of the present invention still fall within the scope of protection of the present invention.

[0034] Example 1

[0035] The process of preparing the MeO-2PACz self-assembled monolayer in this embodiment is as follows:

[0036] Step 1: dissolving a certain amount of carbazole phosphoric acid molecule MeO-2PACz in isopropanol solvent to obtain a MeO-2PACz solution with a concentration of 0.5 g / L.

[0037] Step 2: Place the MeO-2PACz solution in an oscillator and stir for 1-2 hours, then spin-coat it on an ITO transparent conductive substrate at a speed of 3000 rpm for 30 seconds. After the spin coating is completed, transfer the substrate to a hot plate at 100° C. and anneal for 10 minutes to obtain a MeO-2PACz self-assembled monolayer.

[0038] Comparative Example 1

[0039] This comparative example is basically the same as Example 1, except that the solvent for preparing the dissolving solution is replaced by ethanol instead of isopropanol.

[0040] Comparative Example 2

[0041] This comparative example is basically the same as Example 1, except that the solvent for preparing the dissolving solution is replaced by acetone instead of isopropanol.

[0042] Application Example 1

[0043] A semi-transparent perovskite solar cell comprises an ITO transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an ITO transparent electrode arranged layer by layer, wherein the hole transport layer is a self-assembled monolayer prepared according to the method of the present invention, i.e., a self-assembled monolayer hole transport layer. The preparation method of the semi-transparent perovskite solar cell is as follows:

[0044] (1) Cleaning the substrate

[0045] The ITO transparent conductive substrate was cleaned with detergent, deionized water and ethanol ultrasonically for 15 minutes and dried, and then placed in a UV light cleaning machine for 15 minutes to obtain a clean ITO transparent conductive substrate.

[0046] (2) Preparation of self-assembled monomolecular hole transport layer

[0047] According to the methods in Example 1 and Comparative Examples 1-2, a self-assembled monomolecular hole transport layer was prepared on a clean ITO transparent conductive substrate.

[0048] (3) Preparation of perovskite layer

[0049] The prepared self-assembled monomolecular hole transport layer was transferred to a nitrogen glove box, and 50 μL of the filtered perovskite precursor solution was measured and spin-coated on the above hole transport layer. The spin coating speed was 4000 rpm, and the spin coating time was 35 s. 120 μL of ethyl acetate anti-solvent was added at the 10th second before the end of spin coating (i.e., 25 seconds). Then, the substrate and the film were immediately transferred to a hot plate at 100°C for annealing for 20 minutes. The main component of the perovskite precursor solution used for spin coating is Cs 0.05 FA 0.73 MA 0.22 PbI2.31 Br 0.69 , and its concentration is 1.5 M. The solvent used to prepare the precursor solution is a mixture of DMF and DMSO in a volume ratio of 4:1.

[0050] (4) Preparation of electron transport layer

[0051] Using a vacuum evaporator, C60 with a thickness of 23 nm was prepared on the perovskite layer as an electron transport layer.

[0052] (5) Preparation of buffer layer

[0053] Using atomic layer deposition equipment, SnO2 with a thickness of 20 nm is deposited on the electron transport layer as a buffer layer.

[0054] (6) Preparation of TCO transparent electrode

[0055] Using a magnetron sputtering device, ITO with a thickness of 200 nm was sputtered on the buffer layer as a transparent electrode.

[0056] Application Example 2

[0057] Referring to the method of Application Example 1, a Figure 8 The semi-transparent perovskite solar cell small module shown has a size of 5*5 square centimeters and an effective area of ​​10 square centimeters. The specific process is as follows:

[0058] (1) Etching P1

[0059] According to the designed size, the ITO transparent conductive substrate is cut using laser scribing equipment.

[0060] (2) Cleaning the substrate

[0061] The ITO transparent conductive substrate after etching P1 was cleaned with detergent, deionized water and ethanol ultrasonically for 15 minutes and dried, and then placed in a UV light cleaning machine for 15 minutes to obtain a clean ITO transparent conductive substrate.

[0062] (3) Preparation of hole transport layer

[0063] According to the method in Example 1, a self-assembled monomolecular hole transport layer was prepared on a clean ITO transparent conductive substrate.

[0064] (4) Preparation of perovskite layer

[0065] Referring to the method in Application Example 1, a perovskite light absorbing layer with a band gap of 1.68 eV was prepared.

[0066] (5) Preparation of electron transport layer

[0067] A C60 electron transport layer with a thickness of 23 nm was prepared on the perovskite layer using a vacuum evaporator.

[0068] (6) Preparation of buffer layer

[0069] A SnO2 buffer layer with a thickness of 20 nm was deposited on the electron transport layer using an atomic layer deposition device.

[0070] (7) Etching P2

[0071] The perovskite layer, electron transport layer and buffer layer prepared in the above process are scribed and cut using laser scribing equipment.

[0072] (8) Preparation of TCO transparent electrode

[0073] A magnetron sputtering device is used to sputter an ITO transparent electrode with a thickness of 200 nm on the buffer layer etched with P2.

[0074] (9 Etching P3

[0075] The ITO transparent electrode is cut using a laser scribing device to obtain a small module of a semi-transparent perovskite solar cell.

[0076] In order to fully understand the performance of the MeO-2PACz self-assembled monolayer and the semi-transparent perovskite solar cell prepared in each embodiment, comparative example and application example, samples were taken for X-ray electron spectroscopy test, water contact angle test, perovskite solution contact angle test, perovskite layer morphology analysis test, ITO conductive substrate MeO-2PACz coverage test, perovskite solar cell performance and stability test. The specific test results are shown in the figure. Figure 1-9 shown.

[0077] Figure 1 The X-ray photoelectron spectra of MeO-2PACz self-assembled monolayers on ITO conductive substrates prepared using different solvents in Example 1 and Comparative Examples 1-2 are shown in FIG. As can be seen from the figure, MeO-2PACz self-assembled molecules prepared using different solvents can be successfully combined on the ITO substrate.

[0078] Figure 2-3 The water contact angle of the MeO-2PACz self-assembled monolayer prepared with different solvents in Example 1 and Comparative Examples 1-2 and the contact angle of the perovskite precursor solution (see Application Example 1) are shown respectively.

[0079] Table 1 Contact angle comparison table of different self-assembled monolayers

[0080] Water contact angle Contact angle of perovskite precursor solution Example 1 (IPA) 53.3° 14.7° Comparative Example 1 (EtOH) 57.7° 17.7° Comparative Example 2 (AC) 40.7° 11.2°

[0081] Depend on Figure 2-3As can be seen from Table 1, the solvent can significantly affect the surface properties of the MeO-2PACz self-assembled monolayer. When ethanol is used as the solvent, the contact angles of water and perovskite precursor solution on the MeO-2PACz self-assembled monolayer are large; when acetone is used as the solvent, the contact angles of water and perovskite precursor solution on the MeO-2PACz self-assembled monolayer are very small; only when isopropanol is used as the solvent, the contact angles of water and perovskite precursor solution on the MeO-2PACz self-assembled monolayer are the most moderate and appropriate.

[0082] Figure 4 The coverage density diagram of MeO-2PACz self-assembled monolayer on ITO conductive substrate prepared by different solvents in Example 1 and Comparative Examples 1-2 is as follows: First, CV test is performed on each self-assembled monolayer sample to obtain the oxidation peak current at different voltage scanning rates, and then the equation is used to calculate the peak current of the oxidation peak current at different voltage scanning rates. The number of adsorbed molecules per unit area is calculated. Figure 4 It can be seen that the MeO-2PACz self-assembled monolayer prepared using isopropanol as the solvent has the most molecules bound per unit area on the ITO conductive substrate, is the most dense, and has the largest coverage, while the MeO-2PACz self-assembled monolayer prepared using ethanol as the solvent has the least molecules bound per unit area on the ITO conductive substrate, is the least dense, and has the smallest coverage.

[0083] Figure 5 The following is a SEM image of the perovskite buried interface of the MeO-2PACz self-assembled monolayer deposited on the ITO conductive substrate using different solvents in Example 1 and Comparative Examples 1-2. Figure 5 It can be seen that the buried surface of perovskite deposited on the MeO-2PACz self-assembled monolayer prepared using isopropanol as solvent is denser and has no holes, while the buried surface of perovskite deposited on the MeO-2PACz self-assembled monolayer prepared using ethanol as solvent is not dense, and there are many voids and gaps between the perovskite grains. At the same time, the perovskite grain size on the buried surface of perovskite deposited on the MeO-2PACz self-assembled monolayer prepared using acetone as solvent is smaller.

[0084] Figure 6 This is the current-voltage diagram of the semi-transparent perovskite solar cell prepared in Application Example 1. All battery devices were tested under the AM 1.5G standard one-sunlight simulation irradiation, with a scan rate of 100mV / s and an aperture of 0.16cm 2 .Depend on Figure 6It can be seen that the performance of the semi-transparent perovskite solar cell device prepared based on isopropanol solvent is significantly better than that of the semi-transparent perovskite solar cell device prepared based on ethanol and acetone solvents. This shows that choosing isopropanol as the solvent for preparing MeO-2PACz self-assembled monolayer can effectively improve the film quality of perovskite and the performance of semi-transparent perovskite solar cells.

[0085] Figure 7 This is the MPP output diagram of the semi-transparent perovskite solar cell prepared in Application Example 1 under the irradiation of LED light simulating sunlight at the maximum power point. The test was carried out in ambient atmosphere and temperature, using a 1000mW / cm 2 The LED continuously illuminates. Figure 7 It can be seen that the semi-transparent perovskite solar cell device made based on isopropanol solvent still maintains 90% of the original device's initial efficiency after 1400h of continuous testing at the maximum power point under an LED lamp simulating sunlight, and has good stability.

[0086] Fig. 9 This is the current-voltage diagram of the semi-transparent perovskite solar cell small module prepared in Application Example 2. The battery module device was tested under the AM 1.5G standard one-sunlight simulation irradiation, with a scan rate of 100mV / s and an aperture of 10cm 2 .from Fig. 9 It can be seen that the MeO-2PACz self-assembled monolayer prepared in Example 1 can be used as an excellent hole transport layer for a small module of a semi-transparent perovskite solar cell. Therefore, the present invention is of great significance for the future commercial production of efficient and stable semi-transparent perovskite solar cells.

Claims

1. A method for preparing an ordered self-assembled monolayer, characterized in that The method comprises: uniformly mixing a carbazole phosphate compound with a solvent to form a film, followed by sufficient annealing; the carbazole phosphate compound is specifically a nitrogen-containing heterocyclic phosphoric acid derivative, including MeO-2PACz, 2PACz, and Me-4PACz, and the solvent is selected from at least one of ethanol, isopropanol, and acetone.

2. The method according to claim 1, characterized in that: The carbazole phosphate compound is specifically MeO-2PACz, and the solvent is specifically isopropanol. The concentration of the solution formed by mixing the two is 0.3-1 g / L.

3. The method according to claim 1, characterized in that: The film is formed on the substrate by spin coating, the rotation speed during spin coating is 2000-5000rpm, and the annealing temperature is 90-140℃.

4. A self-assembled monolayer, characterized in that: The self-assembled monolayer is prepared according to any one of the methods of claims 1-3.

5. The self-assembled monolayer according to claim 4, characterized in that: The water contact angle of the self-assembled monolayer is no higher than 60°, and the number of molecules covered per square centimeter is greater than 10 15 .

6. A semi-transparent perovskite solar cell, characterized in that: The semi-transparent perovskite solar cell has a multi-layer composite structure, including a transparent conductive substrate layer, a self-assembled monolayer, a perovskite light absorbing layer, an electron transport layer, a buffer layer and a TCO transparent electrode layer arranged in sequence, wherein the transparent conductive substrate is specifically an ITO transparent glass substrate, the self-assembled monolayer is specifically the self-assembled monolayer described in claim 4, and the perovskite light absorbing layer is specifically Cs 0.05 FA 0.73 MA 0.22 PbI 2.31 Br 0.69 layer, the electron transport layer is specifically a C60 layer, the buffer layer is specifically a SnO2 layer, and the TCO transparent electrode layer is specifically an ITO transparent electrode.

7. The semi-transparent perovskite solar cell according to claim 6, characterized in that: The thickness of the electron transport layer is 20-30 nm, the thickness of the buffer layer is 10-30 nm, and the thickness of the TCO transparent electrode layer is 100-300 nm.

8. The method for preparing the semi-transparent perovskite solar cell according to claim 6, characterized in that The method comprises the following steps: firstly, preparing a self-assembled monolayer on a transparent conductive substrate, then preparing a perovskite light-absorbing layer on the self-assembled monolayer by spin coating, then preparing an electron transport layer on the perovskite light-absorbing layer by vacuum evaporation, then preparing a buffer layer on the electron transport layer by atomic deposition, and finally preparing a TCO transparent electrode layer on the buffer layer by magnetron sputtering.

9. The preparation method according to claim 8, characterized in that: The perovskite light-absorbing layer is obtained by spin coating a perovskite precursor solution with a concentration of 1.4-1.6M on a self-assembled monolayer and annealing.

10. The preparation method according to claim 9, characterized in that: The rotation speed during spin coating is 3000-5000 rpm, the total spin coating time is 30-50 s, ethyl acetate anti-solvent needs to be added to the wet film surface 10-15 s before the end of spin coating, the annealing temperature after spin coating is 90-120° C., and the annealing time is 20-50 min.

Citation Information

Cited By

  • Mixed self-assembly molecular hole transport layer and preparation method and application thereof

    CN120379445A

  • A hybrid self-assembled molecular hole transport layer, and a preparation method and application thereof

    CN120379445B

  • Large-area uniform strong bonding hole transport layer and preparation method, perovskite solar cell

    CN122825640A